Dr. Vincent Nguyen — Deep Plane Facelift - Nguyen, Vincent (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Vincent Nguyen, France. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003093; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; france